Cord Entanglement in Monoamniotic Twin Pregnancy: A Case Report and Review of the Literature - Ayşe Figen Türkçapar; Berna Seçkin; Ayla Sargın Oruç (Medical Network, 2016)
Monoamniotic twin gestations have been associated with increased perinatal mortality rates of up to 30-50%. Umbilical cord entanglements, twin-to-twin transfusion syndrome, congenital malformations, intrauterine growth restriction, and prematurity are responsible for the high perinatal morbidity and mortality. Cord entanglement can potentially compromise the cord blood flow and cause fetal demise. There is still no consensus on the antenatal management and timing of delivery of these rarely encountered cases. Here, we present a case of monoamniotic twin pregnancy with cord entanglement diagnosed in labour in a 21-year-old primigravid woman and review the obstetric literature about the management of monoamniotic twin pregnancies.